22.2k views
4 votes
Write a coordinate rule for the translation of f(x) to g(x).

(x, y) → (x + 4, y – 5)


(x, y) → (x + 5, y – 4)


(x, y) → (x – 4, y + 5)


(x, y) → (x – 5, y + 4)

Write a coordinate rule for the translation of f(x) to g(x). (x, y) → (x + 4, y – 5) (x-example-1
User Rlz
by
5.8k points

1 Answer

6 votes

(x, y) → (x, y + n) - translate the graph n units up

(x, y) → (x, y - n) - translate the graph n units down

(x, y) → (x - n, y) - translate the graph n units left

(x, y) → (x + n, y) - translate the graph n units right

---------------------------------------------------------------------------

Look at the picture.

(x, y) → (x - 5; y + 4)

Write a coordinate rule for the translation of f(x) to g(x). (x, y) → (x + 4, y – 5) (x-example-1
User Mistercake
by
5.4k points